An interpretative review of a Spanish pioneering doctoral thesis (1855) about the need of travels to complement medical education - Antonio Fernández Cano; Inés Mª Fernández-Guerrero; Cristina Fernández-Guerrero (Revista Española de Educación Médica)
Abstract: The purpose of this work is to inquire into the background of medical education by reviewing a Spanish doctoral thesis from 19th century which highlighting the current interest of the topic of medical education travel.